If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.33 = h + 0.4 Reorder the terms: 0.33 = 0.4 + h Solving 0.33 = 0.4 + h Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '-1h' to each side of the equation. 0.33 + -1h = 0.4 + h + -1h Combine like terms: h + -1h = 0 0.33 + -1h = 0.4 + 0 0.33 + -1h = 0.4 Add '-0.33' to each side of the equation. 0.33 + -0.33 + -1h = 0.4 + -0.33 Combine like terms: 0.33 + -0.33 = 0.00 0.00 + -1h = 0.4 + -0.33 -1h = 0.4 + -0.33 Combine like terms: 0.4 + -0.33 = 0.07 -1h = 0.07 Divide each side by '-1'. h = -0.07 Simplifying h = -0.07
| 165u-4= | | 68-2x=79-3x | | t-23.5=39.7 | | 36=(8)-(14x) | | 0.05m=13.80 | | 9.2=-5g-23.3 | | (-3x)-(7)=23 | | 65-x=180 | | 9+2x=49 | | (-3x)-(7)=3 | | [5x]-7=14 | | abs(5x-4)=-6 | | 9x-4=72 | | 15m+6.3=9.8 | | abs(5x-4)=6 | | Y=7.5+0.5x | | 12y=-48+4x | | 4+12x=112 | | 2(3x+1)-x=3 | | B-(2)=-11 | | 14-4y=y+x | | 1n+3-1=8 | | y-34=41/11(20-6) | | 3x-24=2x+26 | | y-34=41/11(18-6) | | 14x^2+9x=-1 | | -4+6(x-4)=15x+2-9x | | y-4/3-7=.25 | | 6n+3(n+2)=-(2n+7)+n | | -6m=42 | | 5x(2x+7)=2 | | 14x-8=34 |